Operation Matador World War II : Britain's attempt to foil the Japanese invasion of Malaya and Singapore - Ong, Chit Chung (Military classics, 2011)
'Operation Matador' was the code name for Britain's WW2 plan to defend Singapore by holding the whole of the Malayan mainland. This involved entering southern Thailand to forestall Japanese landings on her eastern coastline. Singapore's seaward defences were well developed for the protection of the naval base unlike landward defence. British plans for the latter were considered as early as 1918, 24 years before the actual Japanese landings in southern Thailand and northeast Malaya. However, while 'Operation Matador' was approved as a contingency plan, the resources for its implementation, especially in aircraft, were never made available. As events soon showed, sending naval ships Prince of Wales and Repulse proved a woefully inadequate counter to superior Japanese air power which sank the ships in December 1941 off the east coast of Malaya. This signalled the start of the Japanese invasion and occupation of Malaya and Singapore for the next three years. Dr Ong presents a gripping account of the historical events that went on behind the scenes that delayed and effectively prevented the launch of 'Operation Matador'.